Numerical Analysis of Conductor Galloping Limitation by Oscillation Frequency Detuning - I. I. Serguey; P. I. Klimkovich; A. A. Vinogradov (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
A numerical method has been developed for calculation of conductor oscillations at the moment of galloping that takes account of pendulum  oscillation dampers in the form of eccentric loads. The method is recommended for a numerical analysis of various schemes pertaining to arrangement of horizontal pendulums in the span and their parameters including angles of their initial setting. The obtained results can be used for designing and operation of aerial power lines.